Effect of catalyst and solvent on the Claisen-Schmidt condensation reaction between benzaldehyde derivatives and 2-acetylpyridine - Ratnawati, Devi (UNIB PRESS, 2024)
This study was conducted to observe the effect of catalyst and solvent on the Claisen-Schmidt condensation reaction between benzaldehyde derivatives (compound 1) and 2-acetylpyridine. Chalcones, as compounds with various biological activities, are the focus in the fields of medicine and pharmacology. Efficient and environmentally friendly synthesis methods are essential in the production of these compounds. In this study, the Claisen-Schmidt condensation reaction was used to synthesize the target chalcones. Variations of base catalysts (NaOH and KOH) and solvents (ethanol and methanol) were evaluated to optimize the yield and efficiency of the reaction. The results showed that the use of KOH as a catalyst produced compound 2 with an abundance of 60.47%, which was associated with the stronger nucleophilic nature of hydroxide ions in KOH. In addition, ethanol proved to be a more effective solvent than methanol in this reaction.